THE ROLE OF THE INTERNAL CONTROL SYSTEM IN INCREASING THE RELIABILITY OF ACCOUNTING REPORTS (American Journal of Business Management, Economics and Banking, 2025)
This article focuses on the role of the internal control system in corporate financial management and its significance in improving the reliability of financial reporting. The main components of the internal control system, its potential for reducing errors, preventing financial fraud, and enhancing efficiency through process automation are discussed. The article also highlights the issues of increasing transparency in accounting processes and implementing modern technologies.